Swift mobile platform analysis: - Bolaños-Murillo, Alejandra (Instituto Tecnológico de Costa Rica, 2015)
This is an analysis of Apple’s new programming language: Swift. The investigation takes place in the University of Applied Sciences FH Joanneum in Styria, Austria. A guideline for time and skills administration is written based on the experience developing an iOS mobile application. This application is developed for the administration of an inventory in iPhone and iPad. It is called KMU Inventory App. The outputs of this work are: a document for guiding new developers in this area and the analysis of the hardware and software involved.
KMU Inventory approach
Proyecto de graduación (Licenciatura en Ingeniería en Computadores) Instituto Tecnológico de Costa Rica, Carrera de Ingeniería en Computadores, 2015.
Keywords: Aplicaciones; Lenguajes de Programación; Manejo de Empresas; Teléfonos Móviles; Recuperación de Datos